Association of dietary patterns with depressive symptoms in Chinese postmenopausal women. Issue 10 (26th July 2019) - Liao, Kuan; Gu, Yeqing; Liu, Mingyue; Fu, Jingzhu; Wang, Xiaotong; Yang, Guanlin; Zhang, Qing; Liu, Li; Meng, Ge; Yao, Zhanxin; Wu, Hongmei; Xia, Yang; et al.
Abstract: Many components in diet have regulated oxidative stress, inflammatory reaction and even balance oestrogen levels. Because these factors are closely associated with depressive symptoms in postmenopausal women, it is considered that dietary factors are able to prevent and control depressive symptoms. On the other hand, a dietary pattern that considers the correlations and synergies between foods and nutrients is expected to have a greater impact on disease risk. The aim of the present study is to evaluate whether dietary patterns are associated with depressive symptoms in Chinese postmenopausal women. A cross-sectional study of 2051 postmenopausal women (mean age: 58·8 (sd 7·4) years) was conducted in Tianjin, China. Dietary consumption was assessed by a valid self-administered FFQ. Principal component analysis was used to derive three major dietary patterns: 'healthy', 'sweets' and 'traditional Tianjin' from eighty-eight food items. Depressive symptoms were assessed using the Zung Self-Rating Depression Scale, and cut-off point of 48 indicating serious depressive symptoms. The association between quartile of dietary patterns and depressive symptoms was assessed using multiple logistic regression analysis. The multivariable-adjusted OR of having depressive symptoms for increasing quartile of dietary patterns were as follows: healthy, 1·00, 0·79 (95 % CI 0·49, 1·28), 0·62 (95 % CI 0·37, 1·04) and 0·57 (95 % CI 0·33, 0·97); sweets, 1·00, 0·75 (95 % CI 0·42, 1·3), 1·08 (95 % CI 0·64, 1·81) and 1·66 (95 % CI 1·03, 2·71); and traditional Tianjin, 1·00, 1·02 (95 % CI 0·58, 1·79), 0·96 (95 % CI 0·54, 1·71) and 2·53 (95 % CI 1·58, 4·16), respectively. The present study demonstrated that a healthy dietary pattern was inversely associated with depressive symptoms. On the contrary, greater adherence to sweets and traditional Tianjin dietary patterns was associated with a higher prevalence of depressive symptoms.